A novel moonlight function of glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) for immunomodulation. (28th July 2017) - Nakano, Toshiaki; Goto, Shigeru; Takaoka, Yuki; Tseng, Hui‐Peng; Fujimura, Takashi; Kawamoto, Seiji; Ono, Kazuhisa; Chen, Chao‐Long
Abstract: Glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) is an energy metabolism‐related enzyme, which generates NADH in glycolysis. Our previous study revealed a novel role of exogenous GAPDH in the amelioration of lipopolysaccharide (LPS)‐induced sepsis‐related, severe acute lung injury (ALI) in mice. Here, we show the effect of extracellular GAPDH on the physiological functions of macrophages, which play an important role in the onset of sepsis and ALI. GAPDH has no effect on cell viability, while it strongly suppressed cell adhesion, spreading, and phagocytic function of LPS‐stimulated macrophages. GAPDH treatment significantly reduced tumor necrosis factor (TNF)‐α, while it induced interleukin (IL)‐10 production from LPS‐stimulated macrophages in a dose‐dependent manner. It is noteworthy that heat inactivation of GAPDH lost its immunomodulatory activity. Correspondingly, NADH significantly inhibited TNF‐α and enhanced IL‐10 production with elevation of both M1/M2 macrophage markers. These data suggest that extracellular GAPDH induces intermediate M1/M2 macrophages for termination of inflammation, partly through its enzyme activity for generation of NADH. © 2018 BioFactors, 44(6):597–608, 2018